2010
DOI: 10.1007/s00477-010-0417-9
|View full text |Cite
|
Sign up to set email alerts
|

A spatio-temporal climate-based model of early dengue fever warning in southern Taiwan

Abstract: Dengue Fever (DF) has been identified by the World Health organization (WHO) as one of the most serious vector-borne infectious diseases in tropical and subtropical areas. During 2007, in particular, there were over 2,000 DF cases in Taiwan, which was the highest number of cases in the recorded history of Taiwan epidemics. Most DF studies have focused mainly on temporal DF patterns and its close association with climatic covariates, whereas they have understated spatial DF patterns (spatial dependence and clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 26 publications
2
63
0
Order By: Relevance
“…The rapid transport facilities and frequent visits to infested areas have been confirmed in previous studies [22,47]. Hydrology or physical existing water channels like rivers, streams and canals play an important role in ambient temperature and humidity profile of a locale [48].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The rapid transport facilities and frequent visits to infested areas have been confirmed in previous studies [22,47]. Hydrology or physical existing water channels like rivers, streams and canals play an important role in ambient temperature and humidity profile of a locale [48].…”
Section: Discussionsupporting
confidence: 54%
“…Aedes Aegypti and Aedes Albopictus have overlapping habitat distributions. The sign and strength of climate-DENV associations depend largely on local climate context [22]. Specific and relative humidity increases along the rivers and streams running through urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Raw data usually contain too much noise to display (Riley, 2008;Zhou, 2009;Christakos, 2010;Wang et al, 2011a;Yu et al, 2011). However, because spatio-temporal processes are integrated and based on data from all domains, the study of a single domain would neglect information from the other domains.…”
Section: Methodsmentioning
confidence: 99%
“…28 To date, there has been limited success in developing an operational EWS for dengue, although several studies have shown the potential to develop such a system. [29][30][31] Aims of the study. The objective of this study is to assess the importance of climate and non-climate drivers of interannual variability in dengue fever in southern coastal Ecuador.…”
Section: Introductionmentioning
confidence: 99%